Comparison of daily and intermittent anti tubercular treatment in achieving sputum negativity in newly diagnosed sputum positive Pulmonary tuberculosis patients - Swapnil M., Thorve; Dhamgaye, T. M. (International Journal of Medical Research and Review, 2016)
Introduction: Tuberculosis is a major health problem in India. Sputum positive pulmonary tuberculosis patients expel bacilli for a variable period after the start of treatment. The period of infectivity depends on the drugs, dosage and interval period. Achieving sputum negativity helps in reducing secondary cases. Aim: Comparison of the effectiveness of daily and intermittent anti tubercular treatment in achieving sputum negativity in newly diagnosed sputum positive pulmonary tuberculosis patients without comorbidities. Methods: A prospective study was carried out in BJMC and SGH, Pune. 71 sputum positive pulmonary tuberculosis patients were included in the study. 35 patients received daily treatment and 36 patients received intermittent treatment. Patients were followed up on 15th, 30th, 45th and 60th day of treatment. Results: Mean duration of sputum conversion was 29 days in daily treatment and 44 days in intermittent treatment. Patients on daily regimen have sputum conversion about 15 days earlier as compared to intermittent regimen. (p<0.05). Conclusion: Patients on daily treatment are sputum negative 15 days prior to patients on intermittent treatment. Using daily treatment will decrease the period of communicability. Thus daily treatment will decrease the incidence and prevalence of the disease in a country with heavy burden of tuberculosis. A cost effective approach will be daily treatment during intensive phase and intermittent treatment during continuation phase.